PENGARUH MANAJEMEN BIAYA INTERNAL, INTEGRASI SISTEM INFORMASI DAN KAPASITAS DAYA SERAP TERHADAP INTER ORGANIZATIONAL COST MANAGEMENT DALAM RANTAI PASOKAN (Studi Empiris pada Perusahaan Manufaktur di Provinsi Banten) - Mulyanah Mulyanah; Imam Abu Hanifah; Khoirunnisa Jauharatul Ummah (FEB Universitas Sultan Ageng Tirtayasa, 2016)
This study aimed to examine the effect of internal cost management, integration of information systems and the capacity of absorption of inter-organizational cost management in the supply chain. Of the 125 questionnaires distributed, the number of questionnaires returned was 42 questionnaire (33.6%). The data is processed by using Structural Equation Modeling (SEM) by using a software program Partial Least Square (PLS). This study was conducted in Manufacturing company located in Banten province, with the object of study in all managers. This study uses survey research with primary data collection using the questionnaire.Results from this study revealed that the variable internal cost management, integration of information systems and communication of climate variables, communication networks and the search for knowledge that is part of the capacity of absorption positive effect on inter-organizational cost management in the supply chain. Keywords: Internal Cost Management, Information System Integration, Absorption Capacity and Inter Organizational Cost Management.